A multiscale methodology for small-scale bubble dynamics in turbulence. (May 2022) - Hidman, Niklas; Ström, Henrik; Sasic, Srdjan; Sardina, Gaetano
Abstract: We formulate in this paper a multiscale numerical framework that handles small-scale bubble dynamics in turbulence. Our framework involves bubbles with arbitrary density ratios with the carrier phase. We use a Moving Reference Frame method that follows a bubble to deal with a fast rising of bubbles present at high density ratios between the phases. We use a Proportional Integral Derivative controller to handle an additional acceleration term in the governing equations that stems from the change of a coordinate system from a fixed to a non-inertial one. Our framework accounts for the fact that the dynamics of bubbles are significantly influenced by the unsteadiness of the small-scale turbulent liquid fluctuations that modify the bubble shapes and alter their motion. In addition, we improve and speed up, with at least two orders of magnitude in computational time, the numerical framework recently proposed by Milan et al. (2020). The developed numerical framework can capture processes occurring at time scales even smaller than the Kolmogorov times. It can be applied to droplets, bubbles or particle systems in both laminar and turbulent flows, using any general DNS technique that handles two-phase flows. Highlights: Multiscale numerical framework for small-scale bubble dynamics in turbulence. Methodology for coupling of solvers at different scales. Moving Reference Frame (MRF) to handle fast rising bubbles at large density ratios. Proportional Integral Derivative controller to handle coordinate system change to MRF. Framework handles particle systems in turbulent flows using any general DNS technique.